Retention of etidronate in human, dog, and rat - Kasting, G B; Francis, M D (Journal of bone and mineral research, 1992)
The retention of radioactivity in human, rat, and dog following a single injected dose of radiolabeled etidronate disodium (EHDP) is shown to follow power-law decay curves with similar slopes for times up to 4, 60, and 80 days, respectively. During this period retention declines with time according to a weak inverse power of the time since dosing, with an exponent ranging from -0.05 (dog) to -0.09 (human and rat). Direct analyses of dog bones either 90 days after a single dose or 365 days after cessation of chronic dosing indicate a more rapid bone clearance of EHDP than predicted by the initial power law. Direct skeletal analysis also shows a more rapid loss of radioactivity in the rat between 60 and 365 days, indicative of either a second power law or a terminal exponential phase in the retention function occurring after 60 days. These data are used to estimate the minimum and maximum amounts of drug that would remain in the body following long-term treatment in humans. For the intermittent cyclic EHDP treatment (ICT) regimen for osteoporosis (repeated cycles of 14 daily doses of 400 mg orally followed by 76 days drug free), the projected retention of EHDP after 3 years of treatment is 25-50 times the daily absorbed dose. Thus, for a 60 kg woman with a daily absorbed dose of 12 mg, the retained mass of EHDP would be about 300-600 mg.